2017
DOI: 10.3892/mmr.2017.6656
|View full text |Cite
|
Sign up to set email alerts
|

Araliasaponin II isolated from leaves of Acanthopanax henryi (Oliv.) Harms inhibits inflammation by modulating the expression of inflammatory markers in murine macrophages

Abstract: Araliasaponin II (AS II) is a bioactive compound isolated from Acanthopanax henryi (Oliv.) Harms, a plant widely used in traditional oriental medicine. The present study investigated the anti‑inflammatory effects of AS II using murine macrophages. The effects of AS II on inflammatory mediator and cytokine production in lipopolysaccharide (LPS)‑stimulated RAW 264.7 cells was evaluated. Nitric oxide (NO) and cytokine production were determined using the Griess reagent and an ELISA kit. The expression levels of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The cells were cultured in a humidified incubator with 5% CO 2 atmosphere at 37 °C. The effects of CLE against macrophages were evaluated as described previously 60 . Briefly, to stimulate the cells, the medium was replaced with fresh RPMI 1640 medium followed by the addition of LPS in the presence or absence of CLE for 24 h. The MTS assay was used to determine the viability.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured in a humidified incubator with 5% CO 2 atmosphere at 37 °C. The effects of CLE against macrophages were evaluated as described previously 60 . Briefly, to stimulate the cells, the medium was replaced with fresh RPMI 1640 medium followed by the addition of LPS in the presence or absence of CLE for 24 h. The MTS assay was used to determine the viability.…”
Section: Methodsmentioning
confidence: 99%
“…According to our previous experimental data and previous literature, peak 5 was tentatively identified as anhuienside C [11,12]. Peaks 13,14, and 15 are attributed to the same aglycone ions as that of peak 5; they were tentatively assigned as araliasaponin II, hexaphyloside A, and ciwujianoside C3, respectively, by comparison with known compounds isolated from S. hexaphylla and their families [13][14][15][16][17] Figure S4). The fragmentation of parent ion produced daughter ions at m/z 928.5, 752.5, and 603.2 attributed to the loss of Ara-Glc, Rha, and Glc.…”
Section: Identification and Characterization Of Chemical Constitutionmentioning
confidence: 57%
“…Of note, these specific triterpenoid saponins exhibit various biological activities. For example, akebia saponin D can suppress both Alzheimer's disease-related neuro inflammation and memory system dysfunction [26,27]; cussonoside A exhibits a pronounced sedative effect [25]; araliasaponin II has strong anti-inflammatory activity [17]. This means that if SHL was chosen to treat Alzheimer's disease, inflammation, insomnia, and other diseases, SHL that was older than three years could be used.…”
Section: Changes In Saponins and Flavonoid In Shl From Different Growmentioning
confidence: 99%
“…Some studies have reported that triterpenoid saponins isolated from the leaves of AH had a significant anti-inflammatory effect [11,20,21,[31][32][33]. For instance, Ciwujianoside C3 (29) exhibited no cytotoxicity at the measured concentrations in RAW264.7 macrophages.…”
Section: Anti-inflammatory Activitymentioning
confidence: 95%
“…Also, it downregulated the expression of interleukin-6 and tumor necrosis factor-α at the protein and mRNA levels. Furthermore, pre-treatment with Araliasaponin II significantly suppressed the TLR-4-NF-κB signaling pathway; this effect may be caused by Araliasaponin II competing with LPS for binding to TLR-4 and subsequently inhibiting translocation of the NF-κB/p65 protein to the nucleus [32].…”
Section: Anti-inflammatory Activitymentioning
confidence: 95%